Assessment of the effectiveness of treatment in patients after acute coronary syndrome - D. A. Shvets; S. V. Povetkin; A. Yu. Karasev; V. I. Vishnevsky (Российский кардиологический журнал)
Aim. To assess the effectiveness of secondary drug prevention and surgical myocardial revascularization in patients with coronary artery disease (CAD) during long-term follow-up after acute coronary syndrome (ACS).Material and methods. The study involved 400 patients with ACS discharged from the hospital in 2012-2016. The diagnosis was verified according to the European Society of Cardiology (ESC) guidelines. There were no exclusion criteria. We analyzed the data of medical records (complaints, medical history, physical examination, laboratory and instrumental data). Repeated data collection was carried out by distance survey and during a face-to-face examination during 2018. According to the clinical course of CAD, all patients were divided into 2 groups. Group 1 consisted of 151 patients with complicated course of CAD, group 2 — 249 patients with stable CAD. We analyzed drug therapy recommended at hospital discharge and taken at the time of the repeated examination. The drug names and daily dosage used for the secondary prevention of CAD were recorded. Assessment of survival without cardiovascular complications was carried out according to the Kaplan-Mayer analysis.Results. Seven-year mortality was 22,5%. The total number of cardiovascular events was 37,7%. The main reason for the frequent complications was the insufficient secondary prevention of CAD after ACS. We found that the drugs and their dosage did not have a significant effect on survival. Statin use is associated with a paradoxical increase in the number of complications. The increased frequency of use and dosage of statins are a consequence of unfavorable course of CAD and do not have the proper preventive effect. For some groups of drugs, we observed irregular intake over the observation period. The low effectiveness of therapy is not only due to insufficient doses, but also in the frequent use of generic drugs. The significant effect of coronary angiography on the probability of cardiovascular complications compared with stenting is due to high proportion of coronary angiography use without revascularization.Conclusion. The combination of following factors of drug therapy can explain the low effectiveness of secondary CAD prevention: low dose (26,1±2,8 mg for atorvastatin), irregular intake and common use of generic drugs (97,6% for statins), present in different ratios. The contribution of surgical treatment to reducing cardiovascular complications is lower, the more significant residual coronary artery stenosis.